Protection of cholinergic and antioxidant system contributes to the effect of Vitamin D3 ameliorating memory dysfunction in sporadic dementia of Alzheimer's type - Marilia Valvassori Rodrigues; Jessié Martins Gutierres; Fabiano Carvalho; Thauan Faccin Lopes; Vitor Antunes; Pauline da Costa; Maria Estér Pereira; Maria Rosa Chitolina Schetinger; Vera M. Morsch; Cinthia Melazzo de Andrade (Taylor & Francis Group, 2019)
Objective: Investigate Vitamin D3 (VD3) effect on the Acetylcholinesterase (AChE), oxidative damage and behavioral tests in animals subjected to Intracerebroventicular injection of Streptozotocin (ICV-STZ) simulating a Sporadic Dementia of Alzheimer's Type (SDAT) and treated with VD3 (21 days). Methods: Animals were divided into eight groups: Vehicle, VD12.5 μg/kg, VD42 μg/kg, VD125 μg/kg, STZ, STZ+VD12.5 μg/kg, STZ+VD42 μg/kg, STZ+VD125 μg/kg. Results: VD3 prevented the increase in AChE in groups of VD42 µg/kg and VD125 µg/kg; in AChE of synaptossomes and TBARS levels prevented the increase in group VD125 µg/kg; in ROS levels there was not a significant difference; for the Carbonyl Content all doses prevented the increase. Total Thiols prevent the decrease in VD42 µg/kg and VD125 µg/kg, and Reduced Glutathione prevented the decrease in VD125 µg/kg, Oxidized Glutathione prevented the increase in VD125 µg/kg. In relation to behavioral tests, the VD3 prevented the increase in time to find (days 2 and 3), in the time to find the platform (day 3) and in time spent in the quadrant (day 2). However, in relation to crossings there was not difference in groups. These results indicated the therapeutic effect of the VD3 in model of STZ in rats.